Nilai-Nilai Pendidikan Intelektual dalam Perspektif Al-Qur'an; Belajar dari Kisah Nabi Ibrahim as - Sahroni; Yeni Setianingsih (DIMAR: Jurnal Pendidikan Islam, 2021)
The Qur'an has a myriad of ways to convey its message to be a lesson for mankind. One is through the method of story. Among the many stories contained in the Qur'an, the story of Ibrahim interesting to observe. Where in the story found intellectual education valuescan be a lesson. By using inductive thinking patterns, Ibrahim teaches us the importance of thinking logically in observing the things that are around us.